Combination of Carbonated Aloe Vera Drink with Lemon Juice - Jefrianta Demu Geri; Dewi Fortuna Ayu; Noviar Harun (JURNAL AGROINDUSTRI HALAL, 2019)
The purpose of this study was to determine the optimal ratio of carbonated aloe vera drink and lemon juice. This research used completely randomized design with four treatments and four replications. The treatments performed were L1 (90% carbonated aloe vera and 10% lemon juice), L2 (80% carbonated aloe vera and 20% lemon juice), L3 (70% carbonated aloe vera and 30% lemon juice), and L4 (60% carbonated aloe vera and 40% lemon juice). Data were statistically analyzed by using analysis of variance (ANOVA) and followed by duncan new multiple range test (DNMRT) at level 5%. The combination treatments of carbonated aloe vera drinks and lemon juice had a significant effect on acidity (pH), vitamin C, total dissolved solids, and descriptive and hedonic sensory assessment. The best treatment from the research was L3 (70% carbonated aloe vera and 30% lemon juice) with pH of 4.26, vitamin C of 19.97 mg, and total dissolved solids of 14.34°brix. The overall sensory test result preferred by panelists with descriptions of yellow color, lemon flavor, and had a slightly sweet taste.